Thực hiện phép tính:
a) (-8,4). 3,2; b) 3,176 - (2,104 +1,18);
c) (2,89 - 8,075) + 3,14.
Thực hiện phép tính:
a)(5x2-2x+1).(2x2-3x)
\(\left(5x^2-2x+1\right)\left(2x^2-3x\right)=10x^4-15x^3-4x^3+6x^2+2x^2-3x\)
\(=10x^4-19x^3+8x^2-3x\)
Bài 3. Thực hiện phép tính:
a) ;= 3.52-16:22
\(3\cdot5^2-16:2^2=3\cdot25-16:4=75-4=71\)
3.52 - 16 : 22
= 3 . 25 - 16 : 4
= 75 - 4 = 71
Câu 1: Thực hiện phép tính:
a) 11/121+(-12/132)+3/123456
\(=\dfrac{1}{11}-\dfrac{1}{11}+\dfrac{1}{41152}=\dfrac{1}{41152}\)
Thực hiện phép tính:
a) 3/5 + 13/25 - 5/9 - 6/14
\(\dfrac{3}{5}+\dfrac{13}{25}-\dfrac{5}{9}-\dfrac{3}{7}\)
\(=\dfrac{15}{25}+\dfrac{13}{25}-\dfrac{35}{63}-\dfrac{27}{63}\)
\(=\dfrac{28}{25}-\dfrac{62}{63}=\dfrac{214}{1575}\)
Thực hiện phép tính:
a) 3/5 + 13/5 - 5/9 - 3/7
`a)3/5+13/5-5/9-3/7`
`=16/5-5/9-3/7`
`=698/315`
3/5 + 13 /5 -5/9 - 3/7 = 698/315
Bài 3. Thực hiện phép tính:
a) 3.52 - 16:22
b) 15.141 59.15
c) 23.17-23.14
Bài 3:
a)3.52-16:22=71
b)15.141+59.15=15(141+59)=3000
c)23.17-23.14=23(17-14)=8.3=24
(câu b hình như thiếu dấu "+"?)
a)3.52-16:22
= 3. 25 - 16 :4
= 75 - 4
= 71
b)15.141+59.15
= 15.(141+59)
= 15. 200
= 3000
c)23.17-23.14
= 23 .(17-14)
= 8 . 3
= 24
Thực hiện phép tính:
a. 17.85 + 15.17 - 120
b. 5.72 - 24:23
c. 33.22 - 27.19
a. `17.85+15.17-120`
`=17 . (85+15)-120`
`=17 . 100-120`
`=1700-120`
`=1580`
b. `5.7^2 - 24 : 2^3`
`=5. 49 - 24: 8`
`=245-3`
`=242`
c. `3^3 .22 -27.19`
`=27.22 - 27.19`
`=27 . (22-19)`
`=27.3=81`
a. 17.85 + 15.17 - 120
=17(85+15)-120
=17.100-120
=1700-120
=1580
b. 5.72 - 24:23
=5.49-24:8
=245-3
=242
c. 33.22 - 27.19
=27.22-27.19
=27(22-19)
=81
Thực hiện phép tính:
a)3200:40.2 b)3920:28:2 c)(34.57 - 92.21):35
1.3200 : 40 . 2 = 80 . 2 =160
2,3920:28:2= 70
3.....=12
a: \(3200:40\cdot2=160\)
b: \(3920:28:2=70\)
c: \(\left(3^4\cdot5^7-9^2\cdot21\right):3^5=3^2\cdot5^7-7=703118\)
Thực hiện phép tính:
A=3.1/1.2−5.1/2.3+7.1/3.4−...+15.1/7.8−17.1/8.9
Dạng tổng quát: \(\dfrac{a+b}{ab}=\dfrac{1}{a}+\dfrac{1}{b}\)
Áp dụng:
\(A=\dfrac{3}{1.2}-\dfrac{5}{2.3}+\dfrac{7}{3.4}-...+\dfrac{15}{7.8}-\dfrac{17}{8.9}\)
\(=\left(1+\dfrac{1}{2}\right)-\left(\dfrac{1}{2}+\dfrac{1}{3}\right)+\left(\dfrac{1}{3}+\dfrac{1}{4}\right)-...+\left(\dfrac{1}{7}+\dfrac{1}{8}\right)-\left(\dfrac{1}{8}+\dfrac{1}{9}\right)\)
\(=1+\dfrac{1}{2}-\dfrac{1}{2}-\dfrac{1}{3}+\dfrac{1}{3}+\dfrac{1}{4}-...+\dfrac{1}{7}+\dfrac{1}{8}-\dfrac{1}{8}-\dfrac{1}{9}\)
\(1-\dfrac{1}{9}=\dfrac{8}{9}\)